STUDI KOMUNITAS PADANG LAMUN DI PERAIRAN PANTAI WINI - Ludgardis Ledheng; Vinsensia Ulia Rita Sila (Partner, 2017)
Field Ekosistem ponder to represent the part of coastal area ekosistem and sea which is located in clear and territorial water at deepness gyrate 1 - 12 metre. Ecologically field ponder to have important role to coastal territorial water coastal area region of Wini as detritus prosuden and hara, soft sediment penstabil and fastener, place go out to sea and also sea biota haven. This research, to know field community structure ponder variety, type dominansi and ponder in coastal territorial water of wini. This research represent research of observation by performing perception to know variety, type dominansi and ponder. Result of research indicate that there are 4 type ponder that is Enhalus acoroides, Ovalis Halophila, Syringodium Isoetifolium and Halodule uninervis with gyration variety index 1,01-192, index keseragaman of gyration 0,44-0,74 and gyration dominansi index 0,30-0,61. Condition of community ponder to reside in at labile condition.Â Keyword : Seagrass beds, Diversity index ( H), Evenness index ( E), Domination index ( D)